Pharmacokinetics of a new drug based on polysaccharide from acorus calamus in an experiment on laboratory animals - S. V. Krivoshchekov; E. A. Yanovskaya; R. V. Gurto; O. S. Bryushinina; D. A. Isakov; A. V. Zykova; Yu. G. Zyuz’kova; A. M. Guryev; V. V. Udut; M. V. Belousov (Разработка и регистрация лекарственных средств)
Introduction. α(1,2)-L-rhamno-α(1,4)-D-galactopyranosyluronane is a water-soluble heteropolysaccharide isolated from the rhizomes of calamus marsh (Acorus calamus L.) and has antitumor, antimetastatic, immunomodulatory and hepatoprotective effects, protective effect on hematopoiesis suppressed during cytostatic treatment.Aim. Validation of the bioanalytical method for the determination of α(1,2)-L-rhamno-α(1,4)-D-galactopyranosyluronane Acorus calamus L. and the study of the pharmacokinetic parameters of a new drug based on it after a single administration of 120 mg/kg to rats and 24, 30, 42 mg/kg to rabbits.Materials and methods. In the study, 8 male rats (average weight – 300 g) were used as the main animals. 6 male rabbits (average body weight – 2.5 kg) were used as an additional animal species. The dose assessment experiment was carried out on 24 rabbits (body weight – 2.3–2.5 kg). The quantitative determination of α(1,2)-L-rhamno-α(1,4)-D-galactopyranosyluronane Acorus calamus L. in the blood plasma of animals was carried out by HPLC-MS/MS, the analytical form was galacturonic acid. The method of sample preparation of biological samples included the stage of enzymatic hydrolysis of α(1,2)-L-rhamno-α(1,4)-D-galactopyranosyluronane Acorus calamus L. with a solution of pectinase for the formation of galacturonic acid.Results and discussions. The pharmacokinetics of the new drug α(1,2)-L-rhamno-α(1,4)-D-galactopyranosyluronane Acorus calamus L. was studied after a single dose of 120 mg/kg to rats and 24, 30, 42 mg/kg to rabbits. The average residence time of the drug in the rabbit's body was 1.0 ± 0.21 hours, the half-life was 0.7 ± 0.15 hours. The average residence time of the drug in the rat body was 1.16 hours, the half-life T1/2 was 0.80 hours. After a single intravenous administration to rabbits of 24, 30 and 42 mg/kg, the maximum concentration in the systemic bloodstream is reached 5 minutes after administration and averages 133.95 ± 27.04, 145.86 ± 40.90 and 226.13 ± 41.27 µg/ml, respectively, the half-life ranged from 0.22 to 0.26 h, the half-life from 3.52 to 3.96 hours.Conclusion. The pharmacokinetic parameters of α(1,2)-L-rhamno-α(1,4)-D-galactopyranosyluronane Acorus calamus L. were evaluated in animals based on the use of the method of quantitative determination of galacturonic acid by HPLC-MS/MS.